The Revolutionary Pulp Fiction *: Ernst Fischer’s ‘Lenin’ (1928) and ‘Der große Verrat’ (1950) - Perica, Ivana (Wiener Digitale Revue, 2022)
In her contribution, Ivana Perica shows that Vienna of the 1920s and 1950s had a particular way of dealing with ‘Avant-Garde and Kitsch’ (Clement Greenberg): certainly, kitsch forms go hand in hand with reactionary political forces. But what was progressive art supposed to be an organ for when there was a complete lack of revolutionary consciousness? It is this diagnosis the study of Ernst Fischer’s theatre works Lenin (1928) and Der große Verrat (The Great Treason, 1950) starts with, demonstrating the failure of revolutionary ‘pulp fiction’ in the 1920s and 1950s Vienna: It neither reached the elites nor the masses. Wie Ivana Perica in ihrem Beitrag ausführt, war der Umgang mit ‚Avant-Garde und Kitsch‘ (Clement Greenberg) im Wien der 1920er und 1950er Jahre ein besonderer: zweifellos gehen Kitschformen mit den reaktionären politischen Kräften Hand in Hand. Aber wofür sollte progressive Kunst ein Sprachrohr gewesen sein, wenn es gänzlich an revolutionärem Bewusstsein in der Bevölkerung fehlte? An dieser Feststellung setzt die Untersuchung über Ernst Fischers Stücke Lenin (1928) und Der große Verrat (1950) an und zeigt das Scheitern revolutionärer ‚Pulp Fiction‘ im Wien der 1920er und 1950er Jahre auf: Sie verfehlte sowohl die Eliten als auch die Massen.